Breast milk: friend or FOE?. (7th June 2011) - Shawkat, E; Hussain, N; Myers, J; Gillham, J; Helbert, M
Abstract : Background: Anaphylaxis is potentially fatal and can occur secondary to breast-feeding. Case: On day 3 postpartum, a 30-year-old patient complained of chest tightness, shortness of breath and a rash. She was treated for anaphylaxis and her symptoms resolved. Preceding this event, she had taken tramadol, which raised the suspicion of a drug reaction and the medication was stopped. Despite this action, she experienced further episodes related to breast-feeding and the possibility of breast-feeding induced anaphylaxis was considered. This was confirmed with a lactation challenge. The patient was able to continue breast-feeding with regular feeds and antihistamine with effective control of her symptoms. Conclusion: There are four previously reported cases of breast-feeding induced anaphylaxis. Two case reports describe breast-feeding induced anaphylaxis on day 3 postpartum associated with ibuprofen. The ibuprofen was stopped and on day 4 postpartum both women were able to breastfeed without further reactions. In the other two cases, the women required suppression of breast-feeding. The pathophysiology is unknown but it may be due to an immune response to a component of the breast milk. There are reports of Jersey cattle developing an allergy to the α-casein in their own milk. If milking is delayed, the high intra-mammary pressure forces this protein into the bloodstream where it is recognised as a foreign antigen, stimulating an antibody response. Further leakage precipitates an immediate hypersensitivity reaction. We describe the first case of persistent anaphylaxis to be controlled, enabling the mother to continue breast-feeding.